Food Preferences of Workers of Coptotermes formosanus (Isoptera: Rhinotermitidae) - Mo, Jianchu (Sociobiology, 2014)
Coptotermes formosanus Shiraki is an amphibious termite which severely damages wood components of housing construction, stored cellulose materials, living trees, and communication facilities. The food preference of this termite was investigated in laboratory conditions. Our research results indicated that among 8 kinds of woods (teak Tectona grandis, Chinese fir Cunninghamia lanceolata, oak Quercus mongolica, taxis Melia azedarach, birch Betula allegansis, beech Fagus syliatica, pine Pinus massoniana, and poplar Populus tremula), the consumption rate of pine wood by C. formosanus (30.46%) is higher than that of seven other species of wood. After pine was treated by eight different methods, the pine wood treated repeatedly (three times) by the method of dipping 24 hours in water and drying in the sun (SD method) was significantly preferred by C. formosanus. When adding 30% sugar into water for treatment of pine wood blocks in the SD method, the pine wood blocks attracted more termites to feed compared to other concentrations of sugar in water. Moreover, Adding 10% Formosan subterranean termite nest material into 30% sugar solution increased the preference to the treated pine wood blocks by C. formosanus. This information shows that C. formosanus likes to feed on pine wood blocks treated repeatedly by the method of dipping in mixed solutions of Formosan subterranean termite nest material and 30% sugar for 24 hours and drying in the sun.